The Axial Length and Anterior Chamber Depth in Patients with Cataracts: A Study of Hungarian, Kosovan, and Brazilian Populations - Flaka Shoshi; Andre Messias; Fitore Shoshi; Vinicius Silva Pelicano; Ariana Shoshi; Zoltàn Zsolt Nagy (International Journal of Biomedicine, 2025)
Background: Two crucial parameters to consider when calculating the intra-ocular lens are the axial length (AL) and anterior chamber depth (ACD). This study aims to compare the AL and ACD between Hungarian, Kosovan, and Brazilian patients with cataracts and to predict the possible factors that play a role in these differences. Methods and Results: This comparative cross-sectional observational study included pre-operative biometric parameters, AL and ACD, measured with LenStar900 in patients from Hungary, Kosovo, and Brazil who were scheduled to undergo cataract surgery. We performed biometric measurements of 2043 eyes of patients with cataracts. There was a statistically significant weak negative correlation between age and both biometric parameters (AL and ACD) in Hungarian subjects (P=0.000), while in Kosovar subjects, a statistically significant weak negative correlation was observed only between age and ACD. Unfortunately, this type of analysis was not conducted among Brazilian subjects. A one-way ANOVA with Tukey HSD test showed a statistically significant difference in AL between the Hungarian and Kosovan patients (P=0.0000) and Hungarian and Brazilian patients (P=0.0002); however, no statistically significant difference was found in AL between the Kosovan and Brazilian patients (P=0.7284). There was no statistically significant difference in ACD values between all three groups (P=0.5064). Conclusion: There are statistically significant differences in the AL biometric parameter between the three groups of patients, which could be attributed to demographic and social factors specific to each group. Furthermore, this is the first study to include patients from these three countries.